A40 IDENTIFYING NOVEL ROLES FOR TLR2 SIGNALING IN THE INTESTINAL EPITHELIUM USING ORGANOIDS. (21st February 2022) - Chen, Y; Allaire, J M; Han, X; Yang, H; Crowley, S M; Vallance, B
Abstract: Background: Inflammatory bowel disease (IBD) is thought to result from an imbalance between protective and damaging immune responses to the resident microbiota and other luminal antigens. Increasing evidence suggests that toll-like-receptor (TLR)-mediated innate immune dysfunction contributes to the pathogenesis of IBD. Among the receptors in the TLR family, TLR2 and its signalling pathway appears to play an important protective role in the gastrointestinal (GI) tract. Notably, our group previously discovered that Tlr2 expression by nonhematopoietic cells played an important protective role in the Citrobacter rodentium model of infectious colitis. Aims: To determine if intestinal epithelial cells (IECs) control Tlr2 dependent tissue protective responses, we sought to characterize the role of Tlr2 signalling in intestinal organoids. In addition, to better define the role of Tlr2 during C. rodentium infection, we developed a novel in vitro model of C. rodentium infection using organoid-derived monolayers. Methods: Organoids were derived from the colonic tissue of wild type (C57BL/6J) and Tlr2 deficient ( -/- ) mice and then stimulated with Tlr2 agonists, and their responses were evaluated by qPCR, ELISA, Western blot and immunostaining. In addition, 2D monolayers were grown from organoids, and infected with C. rodentium to explore whether Tlr2 signaling regulates other protective IEC functions such as barrier proteins and cell death in response to noxious stimuli. Results: Stimulation of WT, but not Tlr2 -/- mouse orgnaoids led to increased transcription of chemokine and cytokine genes Ccl20, Mcp-1, Cxcl1 and Tnf-α. This was accompanied by increased protein secretion through a NF-κB and p38 MAP kinase dependent mechanism. Interestingly, organoids derived from the distal colon displayed stronger Tlr2 responses than organoids from the proximal colon. During C. rodentium infection of monolayers, Tlr2 signaling had no effect on the distribution of tight junction proteins such as ZO-1 or Claudin3, however, Tlr2 did regulate levels of IEC apoptosis upon C. rodentium infection. Conclusions: Our study demonstrates that colonic organoids express functional Tlr2, which upon stimulation, leads to pro-inflammatory responses as well as control over cell death. Our novel C. rodentium infection model enables us to further study the role of IEC in promoting host defense during bacterial infection. Futher work will examine how interactions with Tlr2 dependent cytokines (ie. IL-6, IL-22) impact IEC responses to C. rodentium . Funding Agencies: CCC, CIHRCH.I.L.D